2019
DOI: 10.1055/s-0039-1690680
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Hydroamination of Alkynes: A Mild and Concise Synthesis of Thiazolo[3,2-a]indoles and their Cytotoxic Activity

Abstract: A metal-free, mild and efficient method for the synthesis of thiazolo[3,2-a]indoles has been developed starting from indoline-2-thiones. The reaction methodology involves first the formation of thermally labile 2-(prop-2-ynylthio)-1H-indole intermediates, which undergo base-mediated intramolecular hydroamination to produce the title compounds in excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Similar enamines have been elusive in previous studies performed in the absence of strategically located formyl groups. 14,15 In order to gather evidence to support this hypothesis, we subjected the exo product 5a to strongly basic conditions. To our delight, 5a rapidly transformed to endo isomer 6a in the presence of KOH (Scheme 2c).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar enamines have been elusive in previous studies performed in the absence of strategically located formyl groups. 14,15 In order to gather evidence to support this hypothesis, we subjected the exo product 5a to strongly basic conditions. To our delight, 5a rapidly transformed to endo isomer 6a in the presence of KOH (Scheme 2c).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In general, the synthesis of 1,2-fused indoles containing the S atom have not been explored to the same extent as 2,3-fused tricycles. A survey of the literature revealed that only a handful examples for the synthesis of thiazoloindole cores have been reported to date, each using indoline-2-thione as the precursor. ,, In the first case, the treatment of thione with bromoacetaldehyde diethyl acetal followed by polyphosphoric acid resulted in thiazolo­[3,2- a ]­indole formation . The synthesis of benzylated thiazoloindoles was developed based on the sequential S-propargylation-Sonogashira reaction in conjunction with intramolecular cyclization (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…The isolated yields of the corresponding products were obviously improved through path b. [46] Namboothiri and co-workers utilized indoline-2thiones 58 to participate the base-mediated [3 + 2] annulations with Morita-Baylis-Hillman (MBH) and Rauhut-Currier adducts of nitroalkenes. The resulting indole-annulated thiophenes 122 and 124 bearing hydrazine, ketoalkyl, and other functional groups provided opportunities for further synthetic applications (Scheme 32a).…”
Section: Inorganic Base-mediated Annulationmentioning
confidence: 99%
“…When a soft base was used, S ‐propargyl intermediates 119 could be isolated, and the products 120 could be achieved through KOH‐promoted cyclization (Scheme 31b, Path b). The isolated yields of the corresponding products were obviously improved through path b [46] …”
Section: ‐Thioxoindolines As Starting Materialsmentioning
confidence: 99%
“…Recently Jha and co‐workers also reported a similar base mediated intramolecular hydroamination reaction using KOH/DMSO system (Scheme 64). [77a] …”
Section: Metamorphosis Of Heteroarene‐tethered Propargyl Alcohols Andmentioning
confidence: 99%